Analisa Waktu Kerja Rele Arus Lebih Terhadap Letak Gangguan Hubung Singkat Dengan Menggunakan Software ETAP 12.6 - Palagan, Yudha, Umar, S.T., M.T (2016)
Medium voltage network is one of the electric power distribution of the high-voltage network to the consumer, at the voltage medium voltage network will be on for each feeder for distribution. The greater the level of consumer demand, PLN in demand to be able to provide adequate services for consumers. Electric power distribution equipment require reliability in maintaining the distribution of disorders including short circuit. In minimizing the disturbance required protection system that meets the requirements of sensitivity, reliability, selectivity and speed, which are all dependent on the accuracy in protection equipment setting. One of protective devices are in use in the medium voltage network is the overcurrent relay (OCR), which is relay the function of instructing PMT to open so that disturbances in medium voltage networks were disrupted can be separated from electric power distribution systems. This thesis will discuss about the analysis of OCR work time to the location of disruption of the Jajar 5 feeder. Comparison between the results of short circuit fault current calculations and the results of simulations on ETAP 12.6 software will be used as fill to calculate the value of OCR work time on the incoming side and outgoing. The result of the calculation of the maximum short circuit current interruption occurs in the three-phase bus 3 disturbance at 11782 Ampere, while the current minimum short circuit occurs on the bus 8 one phase to ground disturbance at 2948 amperes. Setting OCR on the incoming side got value TMS = 0.295, while the OCR setting on the outgoing side got value TMS = 0.15. Relay work operations simulation results with standard characteristics inverse conducted showed that the greater the fault current relay working time will be faster and as CB are closest to the fault location fails to operate the CB upstream of the other will operate as a backup. This shows that the setting installed in the substation row still in good condition.